ANALYSIS IMPLEMENTATION OF BACK REFERRAL PROGRAM DIABETES MELLITUS AND HYPERTENSION IN HOSPITAL X, JAKARTA - Riza Ambari; Mieke Savitri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Since morbidity rate of Diabetes Mellitus and Hypertension in Indonesia increased, the number of referral in hospital automatically high. National Health Insurance and hospital burden also increase if the Back- Referral Program (BRP) has not been implemented yet. The impact of the ineffectiveness of Back-Referral Program also felt by Hospital